Characterization of melanin and optimal conditions for pigment production by an endophytic fungus, Spissiomyces endophytica SDBR-CMU319 - Suwannarach, Nakarin; Kumla, Jaturong; Watanabe, Bunta; Matsui, Kenji; Lumyong, Saisamorn (PLOS ONE, 2019)
Melanin is a natural pigment that is produced by filamentous fungi. In this study, the endophytic species, Spissiomyces endophytica (strain SDBR-CMU319), produced a brown-black pigment in the mycelia. Consequently, the pigment was extracted from the dried fungal biomass. This was followed by pigment purification, characterization and identification. Physical and chemical characteristics of the pigment showed acid precipitation, alkali solubilization, decolorization with oxidizing agents, and insolubility in most organic solvents and water. The pigment was confirmed as melanin based on ultraviolet-visible spectroscopy, Fourier-transform infrared, and electron paramagnetic resonance spectra analyses. The analyses of the elemental composition indicated that the pigment possessed a low percentage of nitrogen, and therefore, was not 3,4-dihydroxyphenylalanine melanin. Inhibition studies involving specific inhibitors, both tricyclazole and phthalide, and suggest that fungal melanin could be synthesized through the 1,8-dihydroxynaphthalene pathway. The optimum conditions for fungal pigment production from this species were investigated. The highest fungal pigment yield was observed in glucose yeast extract peptone medium at an initial pH value of 6.0 and at 25°C over three weeks of cultivation. This is the first report on the production and characterization of melanin obtained from the genus Spissiomyces.